How might creative learning through dance support resilience?. Issue 3 (2nd April 2020) - Buck, Ralph; Snook, Barbara
ABSTRACT: It is a generally accepted fact that exercise promotes well-being and improves mental and physical health. Research supports the belief that exercise reduces stress, decreases anxiety and reduces depression, arguably fostering resilience. Quantitative research reveals that 'exercise is associated with profound changes in motor, sensory and autonomic regions of the brain'. While our research includes connections to dance as exercise, we extend our research beyond the benefits of exercise, and examine the effects of creative learning through dance as a means for fostering resilience and developing a certain reservoir or 'wealth' of resilience. From the outset it is acknowledged that there is no one way of being resilient nor one way of learning to be more resilient.